Advancing selective copper detection in water: Innovative electrode utilizing surface ion-imprinted polymer - Sheng Gong; Yujie Liang; Xuhong Liu; Huilin Gao; Haiyan Liao; Xiaoqiang Lin; Murtaza Hasan; Xinhua Zhou; Sundaram Gunasekaran (Applied Surface Science Advances, 2023)
Researchers are still faced, with the challenge of creating a readily fabricated ion-imprinted electrode that can quickly and precisely detect trace metal ions. In this paper, a novel surface ion-imprinted polymer (sur-IIP) based on Au nanoparticle with high conductivity was synthesized and modified on the glassy carbon electrode (GCE). From structural characterization, the functional monomer, thiolated chitosan, was self-assembled on the surface of Au nanoparticle by the ‘Au-S’ bond and formed an imprinted layer in 15 nm thick. During the electrochemical measurement, different detection parameters such as supporting electrolyte, pH, deposition potential, deposition time were optimized under the optimal conditions, the modified electrode exhibited a extensive linear range from (0.05–30 μmol L-1) and lowest limit of detection was 0.0487 μmol L-1. The developed sensor was applied for the detection of traces of Cu (II) ions from tap water as well as from drinking water successfully. Compared with other surface ion-imprinted polymers, the sur-IIP in this paper were more conductive and could be modified tightly on the electrode by dip-dropping. The overall strategy of preparing the ion-imprinted polymer on the surface of Au nanoparticles were accessible and efficient.